THE INFLUENCES OF ENTREPRENEUR BEHAVIOR AND GROUP PARTICIPATION AGAINST BUSINESS PERFORMANCE THROUGH MOTIVATION - Irawan, Danny Hendra; Utami, Hamidah Nayati; Abdillah, Yusri (FIA UB, 2018)
Small Medium EnterpriseS (SME) development is one of essentials matters in Indonesia’s economy. One of SME s which currently keeps growing is SME in tourism sector. SME in this sector is the form of people’s economic independence, for example batik craft SME from Blitar which is a tourism product. This research explains about the influence of entrepreneur behavior and group participation against business performance managed by the variable of motivation. This type of research is an explanatory research using questionnaire as a primary data collection tool distributed to the owners of Blitar batik SME s. The sample of this research is saturated sample by making all Blitar batik SME owners as research samples up to 77 respondents. Path analysis using SPSS 20.0 is selected to analyze the influence of the variable in this research. The result of this research shows that entrepreneur behavior and group participation bring positive and significant influences against motivation and business performance.